answersLogoWhite
Math and Arithmetic
Algebra
Calculus

What is -6y plus 7x equals -9?


Top Answer
User Avatar
Wiki User
Answered 2011-01-29 20:11:31

It's the equation of a straight-line graph. Every point on the line is

a solution of the equation. There are an infinite number of them.

001
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
๐Ÿ˜‚
0
User Avatar

Your Answer

Related Questions


It does nothing! 4x + 6y = 24 7x + 6y = 9 Subtracting the first equation from the second gives: 3x = - 15 so that x = -5 Substituting the value of x in the first equation gives -20 + 6y = 24 so that 6y = 44 and so y = 22/3 or 71/3


-7x + 5 = -9 -7x = -14 7x = 14 x = 2


The variables in the given expression are x and y


Subtract 7x from each side: 8 = -9 Not possible, game over.


4x+9 = 7x+3 4x-7x = 3-9 -3x = -6 x = 2


Two ways to see this: 6y=8-9+6y 6y=6y-1 No answer here 6y= 8-(9+6y) 6y+(9+6y)=8 12y+9=8 12y=-1 y= -(1/12) or -0.08333...


No solution. Multiply second equation by 3 and get 12x + 6y = 0 but already stated 12x + 6y = 9...



8x-2 = -9+7x8x-7x = -9+2x=-7


7x + y + z = 6 7x + y + 4z = 9 y + x = 6 Take the first two statements and subtract them. 7x + y + z = 6 7x + y + 4z = 9 _____________ 0 + 0 - 3z = -3 Therefore: z = 1 Then you are left with: 7x + y + 1 = 6 7x + y + 4 = 9 which is impossible, so this is an impossible equation.



-8x+7 = -7x-2 -8x = -7x-2-7 -8x=-7x-9 -8x+7x=-9 -1x=-9 x=-9/-1 x=9



7x - 9 = 3x + 5 7x - 3x - 9 = 5 7x - 3x = 5 + 9 4x = 14 x = 14/4


-9x+6y = 54 6y = 9x+54 y = 1.5x+9 slope = 1.5



-6y + 14 + 4y = 32-2y = 32 - 14-2y = 18y = - 9


x2 + 7x + 9 = 3 ∴ x2 + 7x + 6 = 0 ∴ (x + 6)(x + 1) = 0 ∴ x ∈ {-6, -1}


7x - 2 = 4x + 9 3x - 2 = 9 3x = 11 x = 11/3


11x+9=7x+21 11x-7x=4 4x+9=21 21-9=12 4x=12 12 divided by 4= 3 x=3


7x+3y where x=2 and y=9 can be written as (7*2)+(3*9) which can be simplified to (14)+(27), from there it's basic addition.


If: x+3+6x+9 = 0 then 7x+12 = 0 So: 7x = -12 and x = -12/7


7x-4x+2x+5=2x+14 5x+5=2x+14 3x=9 x=3


4x + y = 9 so that y = 9 - 4x 7x - 8y = 6 7x - 8*(9-4x) = 6 7x - 72 + 32x = 6 39x = 78 x = 2 Then y = 9 - 4x = 9-4*2 = 9-8 = 1


I don't know how, because I'm not good at math, but the answer is;79



Copyright ยฉ 2021 Multiply Media, LLC. All Rights Reserved. The material on this site can not be reproduced, distributed, transmitted, cached or otherwise used, except with prior written permission of Multiply.